The mechanism of current transport in the structure Al-p-CdTe-Mo with different thickness of the base - Mirsagatov, Sh.A.; Uteniyazov, A.K. (Физическая инженерия поверхности, 2015)
In this paper the mechanism of current’s transport in the structure Al-p-CdTe-Mo is studied, when the thickness of the base w ≤ 10 μm. The results of study of current-voltage characteristics of the structure Al-p-Cd-Te-Mo with different thicknesses of the base and the influence of the thickness of the base on the mechanism of current’s transport are given.